VASYL STEFANYK’S PUBLICIST WORKS: THE PORTRAIT DETAILS - Khorob, Solomia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The purpose of the article is to study peculiarities of the publicist speeches (both oral and printed) of Vasyl Stefanyk as this could contribute to his general creative portrait. Research methods include historical, cultural, and biographical ones. The results of the research represent a thorough analysis of certain inquiries, written and oral speeches of Vasyl Stefanyk perceived as important manifestations of his journalistic and socio-political activities, as natural factors of the life and creative work the outstanding writer. The research article proves that they were national-patriotic essence and ideological conviction that dominated a number of his publicist speeches, in particular, during the period of the writer’s deputy service in the Vienna Parliament (1908-1918) and prior to 1908 as well. It also emphasizes that the motives of such inquiries, written and oral speeches come from historical and political, national and social, spiritual and patriotic, as well as common human factors, as their content along with ideological and aesthetic essence were an integral part of the life and work of Vasyl Stefanyk. Scientific novelty: the article focuses on the disclosure of the problem of "journalism of Vasyl Stefanyk" from the standpoint of new methodological approaches, it is studied and clarified according to an updated database of socio-historical and scientific-biographical data on the lives of the Western Ukrainian people on the given period, in particular of Vasyl Stefanyk. The practical significance of the article is that its results can be used in the study of the writer’s work, in particular his journalistic activity.